DEVELOPMENT OF ANTIOXIDANT DERMOCOSMETIC CREAM BASED ON BIOACTIVE COMPOUNDS FROM Chenopodium quinoa Willd. AND Calendula officinalis Vahl - Solano Canchaya, Gabriela N. (2025)
Exposing our skin continuously to ultraviolet radiation can cause conditions such as erythema, premature aging even skin cancer, which can be prevented by using dermocosmetic products with antioxidant activity. The main objective of the study was to develop a dermocosmetic cream enriched with active ingredients coming from hydroalcoholic extract of Chenopodium quinoa Willd. and ethanolic extract of Calendula officinalis Vahl. For that, a phytochemical screening was performed using coloration and precipitation reactions. Then, the cream was prepared and its stability was evaluated by heat shock. Antioxidant activity was determined using DPPH•, ABTS●+, and FRAP methods. The secondary metabolites observed in greatest quantities were polyphenols and glycosides for calendula; and only glycosides for red quinoa. In vitro antioxidant activity using the DPPH• method indicated an IC50 of 27.47 μg/mL, and a TEAC of 92.79 mg Trolox®/g of cream; by the ABTS●+ method, an IC50 of 47.73 μg/mL, and a TEAC of 95.42 mg Trolox®/g of cream; and by the FRAP method, an AAEAC of 6.79 mg Ascorbic acid/g extract. The dermocosmetic cream enriched with red quinoa and calendula extracts demonstrated high antioxidant activity, in addition to complying with stability and extensibility tests.